Teaching the Grammar of Russian Language - Great Opportunities for the Linguistic and Mental Development of Students - Fayzieva Yulduz Yusupovna (Zien Journals, 2023)
Great opportunities for the linguistic and mental development of students include teaching the grammar of Russian language, which enriches them with knowledge of the basic laws and rules of the language system, morphological and syntactic means of expressing thoughts, contributes to the development of logical thinking of students, and is the basis for the formation of practical speech and spelling skills. Based on the analysis of the relevant methodological literature and the study of the experience of teaching Russian language, the need to find optimal conditions for the language development of students is established.
Keywords: significant age; individual variability; language material; components